University drop-outs.:A systemic play of subjects, institutions and macro contexts - Aparicio, Miriam Teresita (2014)
This paper is a part of a wider research program concerning the assessment of quality at University. It was selected by the Department of University Policies (Ministry of Education, Science and Innovation) in an attempt to determine the causes and “reasons” underlying dropping school in our country. The Program includes three sub-projects concerning both academic and socio-professional success, delay and failure (dropping out). Our specific aim here is to determine the psychosocial reasons for failure at University (qualitative aspect). The sample includes University students who quit studies at UNCuyo in a period of nearly 20 years (1987-2004). A quanti-qualitative methodology was applied so as to be able to explain and more fully understand the importance of the causes and the reasons underlying their quitting. 212 indicators were used. Results show different profiles connected with the same variables/psychosocial dimensions (n-ach, expectations, fatalism, self-efficacy, life projects, social representations of the importance of university degrees in relation with insertion in the labor market, etc) underlying drop-outs.